REGULASI ZAKAT BAGI APARATUR SIPIL NEGARA DI INDONESIA - Isnawati Rais; Abdul Halim; Nisrina Mutiara Dewi; Asmawi Asmawi; Ahmad Bahtiar (Universitas Islam Negeri Mataram, 2020)
This study aims at analyzing Islamic and positive laws in Indonesia regarding the obligation of zakat for the Goverment Employee (ASN). This is Important for finding the basis for the state in goverming zakat regulation for Muslim ASN with a payroll cut of 2.5 percent by the Ministry of Religius Affairs as well as for getting arguments in terms of islamic law and politics of law as well as their relation to these regulations. The method used in this study is a qualitative research with a statutory approach with data in the form of zakat laws and regulations enforced in Indonesia, both in terms of religious and state norms. The findings of this study indicate that there are important issues from this regulation in the perspective of Islamic law and politics of law: First, the regulation of zakat obligations for the goverment employees is not in accordance with Islamic law; Second, the method of determining muzaki (zakat payers) by the state is still biased because it declares that all the Muslim goverment employees are Muzaki; Third, the basic calculation for compulsory zakat has not calculated the gross basic needs of the goverment employees and the expenditure of basic needs (hajah ashliyyah) yet.